(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
Simultaneous translation is a critical skill in facilitating communication across different languages in real-time. It requires a deep understanding of both linguistic and extralinguistic factors that affect the quality and accuracy of the translation. Linguistic factors include elements such as syntax, morphology, and semantics, while extralinguistic factors involve aspects like the speaker’s tone, socio-cultural context, and cognitive load.